2012
DOI: 10.7863/jum.2012.31.8.1245
|View full text |Cite
|
Sign up to set email alerts
|

Liver and Spleen Stiffness Measured by Acoustic Radiation Force Impulse Elastography for Noninvasive Assessment of Liver Fibrosis and Esophageal Varices in Patients With Chronic Hepatitis B

Abstract: epatitis B, which is caused by the hepatitis B virus (HBV), is a potential life-threatening liver infection and the most serious type of viral hepatitis. As the World Health Organization reported, 1 approximately 2 billion people have been infected with HBV worldwide, and more than 350 million people have chronic hepatitis B. In China, the most common viral hepatitis is type B. The final evolutionary stage of chronic hepatitis B is liver cirrhosis. Portal hypertension is a major cause of esophageal varices, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 25 publications
5
51
1
Order By: Relevance
“…To combine sensitivity, specificity, and AUROC, 21 articles with 22 studies and 2,691 patients were included in the diagnosis analysis. Of the 21 articles, 11 [15,18,20,22,[26][27][28][29][30]33,35] articles provided ARFI values that were combined in the analysis. Details are present in figure 1.…”
Section: Article Selectionmentioning
confidence: 99%
“…To combine sensitivity, specificity, and AUROC, 21 articles with 22 studies and 2,691 patients were included in the diagnosis analysis. Of the 21 articles, 11 [15,18,20,22,[26][27][28][29][30]33,35] articles provided ARFI values that were combined in the analysis. Details are present in figure 1.…”
Section: Article Selectionmentioning
confidence: 99%
“…Ye et al have reported a significant correlation between spleen elastography and EVs in patients with chronic HBV (sensitivity 84.1%, specificity 81%) [10]. Colecchia et al found significant correlation between spleen elastography and EV in patients with chronic hepatitis C related liver cirrhosis (sensitivity 98.5%, specificity 60.1%, negative predictive value 98.4%) [11].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to measure spleen stiffness by ARFI elastography in patients with chronic liver disease has also been recently reported. However, these stud-ies focused primarily on the simple correlation between spleen stiffness and EVs without consideration of cirrhosis etiology [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…213 Using the Batts and Ludwig scoring system, 214 ARFI had a sensitivity of 68% and specificity of 66% for fibrosis stage ≥2 and a sensitivity of 95% and specificity of 86% for fibrosis stage ≥3 in patients with diverse chronic liver diseases. 215 Spleen stiffness by ARFI has correlated with the grade of oesophageal varices (whereas liver stiffness has not), 216,217 and ARFI, like magnetic resonance elastography, 183 may evolve into a non-invasive method for assessing manifestations of portal hypertension. 216,217 The confounding factors that can affect the performance of ARFI are similar to those affecting tissue elastography (Table 3).…”
mentioning
confidence: 99%
“…215 Spleen stiffness by ARFI has correlated with the grade of oesophageal varices (whereas liver stiffness has not), 216,217 and ARFI, like magnetic resonance elastography, 183 may evolve into a non-invasive method for assessing manifestations of portal hypertension. 216,217 The confounding factors that can affect the performance of ARFI are similar to those affecting tissue elastography (Table 3). Hepatic inflammation, but not hepatic steatosis, 218 increases the ARFI measurements when the fibrosis stage is low.…”
mentioning
confidence: 99%